Integrated transcriptomic and proteomic analysis identified key folate biosynthesis gene in waxy maize - Yanyan Jiao; Yaxing Shi; Hui Dong; Yujing Pan; Hui Liu; Zhiyong Li; Xiaqing Wang; Chunhui Li; Tianyi Wang; Shuai Wang; Ronghuan Wang; Baishan Lu; et al. (Crop Journal)
One-third of the global population is affected by micronutrient deficiency, particularly folate. Although folate synthesis has been relatively well characterized, few folate-related genes in maize have been cloned, and the molecular mechanism regulating folate synthesis in maize remains unclear. In this study, transcriptome and proteome analyses of three waxy maize inbred lines with high, medium, and low folate contents were performed to identify key genes controlling folate biosynthesis. Pairwise comparisons revealed 21 differentially expressed genes and 20 differentially expressed proteins potentially associated with folate biosynthesis in the three lines. Six key folate-associated genes, ZmMocos2, ZmGGH, ZmADCL2, ZmCBR1, ZmSHMT, and ZmPurH, were identified. These genes encode enzymes that potentially function in folate biosynthesis. Functional validation of one of these genes, ZmADCL2, using an EMS mutant (Mut9264) showed that a 4-base insertion in an exon increased the folate content of fresh maize kernels 1.37-fold that of the wild type. ZmADCL2 was considered a potential target for generating maize lines with higher folate content. KEGG enrichment analysis of differentially expressed genes and proteins showed that several pathways in addition to folate biosynthesis were likely indirectly involved in folate metabolism and content (e.g., glycine, serine, and threonine metabolism; purine metabolism; cysteine and methionine metabolism; alanine, aspartate and glutamate metabolism; glutathione metabolism; and pyruvate metabolism. The transcriptome and proteomic data generated in this study will help to clarify the mechanisms underlying folate accumulation and aid breeding efforts to biofortify maize with folate.